The impact of leverage on firm performance: evidence from start- ups in Swedan - Da Silva, Ayrton (Graduate School of Business (GSB), 2025)
This study investigates the impact of leverage on the performance of start‐ups within Sweden's dynamic entrepreneurial ecosystem. Given that fewer than 20% of Swedish start‐ups survive beyond their first decade, the challenges of early-stage financing are particularly acute. Drawing on classical frameworks—namely the trade‐off theory, pecking order theory, and signalling theory—the research situates the role of debt in the context of firms that operate under high uncertainty and limited internal resources. Using a comprehensive population dataset from the Serrano database, which covers 66,069 firms over a 20‐year period (1998–2017), the study employs fixed-effects panel regression to assess the relationship between leverage and key performance metrics. The results reveal that an increase in leverage is associated with statistically significant declines in both sales growth and the industry-adjusted operating income ratio (adjOIR). Specifically, a one-unit increase in lagged leverage corresponds to reductions of approximately 0.280–0.232 percentage points in sales growth and 0.039–0.034 percentage points in adjOIR. Furthermore, the adverse effects are magnified for firms identified as highly leveraged. Effect size analysis indicates that a one standard deviation increase in leverage (approximately 24.06 percentage points) results in a decrease of nearly 6.93 percentage points in sales growth and 0.96 percentage points in operating income ratio. In Swedish Krona terms, this equates to revenue losses ranging between 125 and 166 million SEK across the population of firms. These findings underscore the necessity for start-ups to maintain moderate debt levels to preserve financial flexibility and long-term growth potential, offering critical insights for entrepreneurs, investors, and policymakers.